Interleukin-34 and immune checkpoint inhibitors: Unified weapons against cancer - Alshaebi, Fadhl; Safi, Mohammed; Algabri, Yousif A.; Al-Azab, Mahmoud; Aldanakh, Abdullah; Alradhi, Mohammed; Reem, Alariqi; Zhang, Caiqing (Frontiers in Oncology, 2023)
Interleukin 34 (IL-34) is a factor that predisposes immune suppression in various cancer types due to its essential regulatory involvement in tumor-associated immune cells. The microenvironment of a tumor develops immunosuppression and resistance during the process of cancer formation. Macrophages are among the most common immune cells that infiltrate the tumor milieu given that they are immunosuppressive by nature, the possibility of macrophage-related therapy is being investigated thoroughly using different approaches. Immune checkpoint inhibitors (ICIs) have recently gained attention as a treatment option to combat tumors after the three major cancer standard treatments (surgery, radiation, and chemotherapy). The antibody that acts by inhibiting the function of ICI molecules such as programmed cell death protein 1 (PD-1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) has been proven vital to changing the cancer treatment paradigm. Nonetheless, given that considerable percentages of patients do not respond to current cancer ICIs, new therapeutic targets should be identified. In this review, we present the role of IL-34 in the context of the tumor microenvironment (TME). Additionally, the potential involvement of IL-34 in causing ICI resistance in various cancer types is discussed.